PENGARUH STRATEGI DIFERENSIASI TERHADAP UPAYA MEMBANGUN KEUNGGULAN DAYA SAING BERKELANJUTAN PADA HOTEL THE ROYAL PITAMAHA UBUD - Mandhara Putra Sukawati, Cokorda Gde; Jatra, I Made (E-Jurnal Manajemen, 2015)
The development of tourism in Bali is very tight due to the increasing number of tourists who take advantage of the hospitality services. To maintain business continuity needed some marketing strategies. One strategy that can be selected by the company is product differentiation strategy. This study aims to reveal the effect of differentiation strategy undertaken at The Royal Pita Maha against a competitive advantage with the number of 100 respondents as well as using non-probability sampling method. Data was collected by questionnaire and the data were analyzed using multiple linear regression to examine the effect of the differentiation of competitive advantage berkelanjutan.Hasil research shows that product differentiation and a positive effect on the competitiveness of sustainable real. Results of other studies also found a positive effect on service differentiation and significant to sustainable competitiveness.
Keywords: product differentiation, service differentiation, differentiation imagery, sustainable competitiveness